Interfaith workplace interactions in a Buddhist Temple: A phenomenological study of muslim workers at the Avalokitesvara Temple, Pamekasan, Indonesia - Usmany, Nuri Wahda Salsabila; Tianah, Itaanis; Safitri, Nuri; Iskandar, Iskandar; Ram, St. Wijdanah (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2026)
Interfaith social interaction in the workplace represents a crucial yet underexplored dimension of religious tolerance in plural societies. This study examines the social interactions between Muslim workers and non-Muslim visitors at the Avalokitesvara Temple in Pamekasan, Indonesia, a Buddhist place of worship that employs workers from diverse religious backgrounds. Employing a qualitative phenomenological approach, data were collected through non-participant observation, in-depth interviews with Muslim workers and non-Muslim visitors, and documentation. The findings reveal that social interactions within the temple environment are predominantly associative, characterized by cooperation, accommodation, and mutual respect. Initially driven by economic motives, these interactions gradually developed into broader social relationships grounded in trust, tolerance, and respect for religious differences. Muslim workers demonstrated adaptive strategies, including professional conduct, respectful communication, and boundary awareness during religious rituals, while institutional openness and family support strengthened their sense of comfort and belonging. This study contributes to the literature on interfaith relations by highlighting how everyday workplace interactions can function as a practical arena for fostering religious tolerance and social harmony in multicultural societies.